Effect of friction stir processing on microstructure and microhardness of the 6061 aluminum alloy reinforced with SiCp - H. I. Dawood; Kassim Kadhim Hameed; Kannan Mohammad Musa (Al-Qadisiyah Journal of Pure Science, 2018)
The performance of this study shows that SiCp of particle size 1Î¼m was dispersed into the surface layer of 6061 aluminum alloy sheet by friction stir processing (FSP) technique. The process parameters are rotational speed, traverse speed and axial force and all these parameters kept constant at 1750 rpm, 50 mm/min and 4 kN, respectively. All the specimens were subjected to different numbers of FSP (1 to 3 passes). The effect of FSP passes on the surface metal matrix composites was investigated. The microstructure across the stir zone (SZ) was evaluated by using an optical microscope, and the results showed a banded structure from the particle-rich and particle-free regions of the SiCp. Significant variation in microhardness value of the surface metal matrix composites was observed due to the variation of FSP passes. Higher microhardness value was exhibited when the surface composites were fabricated after 3-pass FSP.